Limited-Duration Cancer Prevalence in Hamburg (1995-2009) : Analysis of Population-Based Hamburg Cancer Registry Data with Comprehensive Investigation of Breast Cancer Prevalence in Women - Wiebke Becker-Hinrichs (2013)
Background: Rising numbers in cancer diagnoses and improving survival, as well as demographic changes, have increased cancer prevalence in Germany. Few data on prevalence on international, national and regional level are yet available. Population-based cancer registries hold valid and reliable data on incidences and follow-up for death and migration. This thesis provides direct calculation of cancer prevalence in Hamburg with an overview of the ten leading cancers in Hamburg for men and women. Detailed analysis of breast cancer prevalence in women is conducted to describe and evaluate temporal trends in prevalence and in relation to incidence. Time-since-diagnosis-groups are formed and correlated to cancer treatment guidelines to estimate minimum health care needs in female breast cancer patients in Hamburg for the year 2009. Methods: Incidence data and follow-up information on death and migration from the population-based Hamburg Cancer Registry and data of residential registration office and the statistical office of Hamburg were linked to calculate 15-year limited-duration point prevalence of 10 leading cancers for men and women in Hamburg. Breast cancer in women was analysed for age distribution, time since- diagnosis and correlated to german up-to-date S3-treatment and follow-up guideline. 5-year partial prevalences were investigated by age, tumour sizes according to TNM-Classification and UICC-stages. 10-year partial prevalences were analysed according to time-since-diagnosis.